APLIKASI CHAT ROOM BERBASIS WEB (Information Technology and Telematics, 2013)
Lately here there is still someone who does not care about having an email. It because some of them think that registrating email was not easy. But, then how they want to send some file to their friend? So, they need some web application with chat and uploading file functions. Using this tool is very simple, easy for everyone. Inside it has multiple chatroom also private chat function. As administrator, he can kick some user. Based on analysis, for someone who does not have email account, sending a file is more effective than using an email. Kata Kunci : Chatting, Chatroom, upload, download, web